A Study of Industrial Liquid Waste Management in PT Pertamina (Persero) Refinery Unit VI Balongan - Alvida Nadira (UHAMKA Press, 2020)
In order to meet people's needs while at the same time improving the environment, the oil and gas industry has a key role to expand the production of crude oil into cruel fuel and non-fuel oil to meet market demand. But, this optimization of crude oil certainly produces a large amount of hazardous liquid waste that is harmful to the environment and public health around the industry.